DESKRIPSI RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR NEGERI 42 PONTIANAK KOTA - Widiawati, Fitria; Halidjah, Siti; Suparjan, Suparjan (Universitas Tanjungpura, 2022)
AbstrakThis study aims to describe the preparation of an online learning implementation planby grade IV teachers at the 42 Pontianak City Elementary School during the Covid-19Pandemic. The research method used is descriptive in the form of qualitative research.The source of the data for this research is the fourth grade teacher of the 42 PontianakCity Elementary School and the data is the online Learning Implementation Plan (RPP)document and the results of interviews with the fourth grade teacher of the 42 PontianakCity State Elementary School. The results of the analysis show that the components ofthe learning implementation plan prepared by the teacher have been guided by the SEKemendikbud Number 14 of 2019 regarding the simplification of the LearningImplementation Plan, but on the completeness and regularity of the componentpreparation there are criteria that are not appropriate for the components of objectives,learning scenarios and learning evaluation. Components that meet the appropriatecriteria are learning media and learning resources. The implementation ofelementsTPACK, HOTS and STEAM of innovative 21st century learning is not described inwriting in the learning step.Keywords: Description, Online Learning Implementation Plan, Themati